Computer Forensics and Cyber Crime Handling - Akay, Yuri V. (Jurnal Teknik Informatika, 2020)
Abstract - Computer forensics is the science of identifying, extracting, analyzing and presenting digital evidence that has been stored in digital devices. For computer crimes in Indonesia, computer forensics is usually carried out regardless of what is inside the computer. In fact, there is more evidence if the computer forensics is identified. There are two methods commonly used for computer forensics, namely search and seizure and discovery information. This method is also developed with evidence management, including the change of custody and rules of evidence. Emphasis on the methods used and what needs, will be discussed on evidence management. Results and conclusions Search and seizures are the most widely used methods, while information retrieval is to complement the evidence data.